‘Ulamā’ and the Formation of Islamic Knowledge: Learning from Two Historical Experiences in Sumatra - Jajat Burhanudin (Jurnal Sejarah Citra Lekha, 2023)
This article discusses the Islamic experiences in two coastal areas of Sumatra, the east and the west coasts, in the late nineteenth and early twentieth centuries. The discussions focus one the ways the difference in the systems of politics created the necessary condition for the rise of two expressions of Islam. The existence of Malay kingdoms in the east coast appeared to be a leading factor in establishment of the kingdom-oriented Islam, different from the stateless condition of the west coast which gave rise to the initial substance of Islamic civil society. In reference to the concept of knowledge formation, this article underscores the two important points of difference, the leadership styles of ‘ulamā’ (Muslim scholars) in the making of Islam and the language expressions they used in their works (kitabs). As such, the study of two areas demonstrates the fact that the real politics appears to have provided the ‘ulamā’ with circumstantial options to engage in certain settings of discourses.